2007
DOI: 10.1007/s10787-006-1542-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitemcinal (GM-611), an orally active motilin receptor agonist, accelerates colonic motility and bowel movement in conscious dogs

Abstract: The prokinetic effects of mitemcinal, an orally active motilin receptor agonist, on the lower gastrointestinal tracts were investigated in conscious dogs. Oral administration of mitemcinal (0.1-1 mg/kg) stimulated colonic motility, which was measured by chronically implanted force-transducers, as well as gastric motility in a dose-dependent manner. The gastrointestinal contractile activities induced by mitemcinal were inhibited by the continuous intravenous infusion of GM-109, a selective motilin receptor anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…14,15 It is being developed by Chugai Pharmaceutical Co., Ltd. as a treatment for gastric motility disorders, diabetic gastroparesis, 16 and colonic motility disorders. 18 The results of this study showed that mitemcinal caused proximal translocation of the GMC starting point and a statistically significant increase in the strength of the GMCs (the GMC index) during the 12-h period after administration. Mitemcinal increased the motor index of the ileum and the colon in parallel with its blood concentration, but it did not increase the motor index of the rectum.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…14,15 It is being developed by Chugai Pharmaceutical Co., Ltd. as a treatment for gastric motility disorders, diabetic gastroparesis, 16 and colonic motility disorders. 18 The results of this study showed that mitemcinal caused proximal translocation of the GMC starting point and a statistically significant increase in the strength of the GMCs (the GMC index) during the 12-h period after administration. Mitemcinal increased the motor index of the ileum and the colon in parallel with its blood concentration, but it did not increase the motor index of the rectum.…”
Section: Discussionmentioning
confidence: 63%
“…Mitemcinal is an erythromycin derivative, and is the first acid‐resistant motilin receptor agonist ever described 14,15 . It is being developed by Chugai Pharmaceutical Co., Ltd. as a treatment for gastric motility disorders, diabetic gastroparesis, 16 and colonic motility disorders 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to the case of motilin, intravenous administration of mitemcinal in dogs [54] stimulated interdigestive, as well as digestive, gastroduodenal motor activity, and its effect was blocked by the motilin-receptor antagonist GM-109. Colonic motility in dogs [55] could also be stimulated by mitemcinal given orally. Randomized controlled trials in 392 insulin-requiring diabetics revealed that symptoms attributable to gastroparesis could be ameliorated with 10 mg mitemcinal twice daily than with a placebo and without inducing significant adverse effects [56].…”
Section: Motilin As a Prokineticmentioning
confidence: 99%